The psychological impact of traffic injuries sustained in a road crash by bicyclists: A prospective study. (3rd April 2017) - Craig, A.; Elbers, N. A.; Jagnoor, J.; Gopinath, B.; Kifley, A.; Dinh, M.; Pozzato, I.; Ivers, R. Q.; Nicholas, M.; Cameron, I. D.
ABSTRACT: Objective : The objective of this study was to investigate the psychological impact of traffic injuries in bicyclists (cyclists) in comparison to car occupants who also sustained traffic injuries. Factors predictive of elevated psychological distress were also investigated. Methods : An inception cohort prospective design was used. Participants included cyclists aged ≥17 years (mean age 41.7 years) who sustained a physical injury ( n = 238) assessed within 28 days of the crash, following medical examination by a registered health care practitioner. Injury included musculoskeletal and soft tissue injuries and minor/moderate traumatic brain injury (TBI), excluding severe TBI, spinal cord injury, and severe multiple fractures. Assessment also occurred 6 months postinjury. Telephone-administered interviews assessed a suite of measures including sociodemographic, preinjury health and injury factors. Psychological impact was measured by pain catastrophization, trauma-related distress, and general psychological distress. The psychological health of the cyclists was compared to that of the car occupants ( n = 234; mean age 43.1 years). A mixed model repeated measures analysis, adjusted for confounding factors, was used to determine differences between groups and regression analyses were used to determine contributors to psychological health in the cyclists 6 months postinjury. Results : Cyclists had significantly better psychological health (e.g., lower pain catastrophizing, lower rates of probable posttraumatic stress disorder [PTSD], and lower general distress levels) compared to car occupants at baseline and 6 months postinjury. Factors predictive of cyclists' psychological distress included younger age, greater perceived danger of death, poorer preinjury health, and greater amount of time in hospital after the injury. Conclusions : These data provide insight into how cyclists perceive and adjust to their traffic injuries compared to drivers and passengers who sustain traffic injuries, as well as direction for preventing the development of severe psychological injury. Future research should examine the utility of predictors of psychological health to improve recovery.